2020
DOI: 10.3390/molecules25215087
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Baicalein, Wogonin, and Oroxylin A on Amyloid Beta-Induced Toxicity via NF-κB/MAPK Pathway Modulation

Abstract: Amyloid beta (Aβ) peptide, one of the most important pathogenic traits of Alzheimer’s disease (AD), invokes a cascade of oxidative damage and eventually leads to neuronal death. In the present study, baicalein, wogonin, and oroxylin A, main active flavones in Scutellaria baicalensis, were evaluated for their neuroprotective effects against Aβ25–35-stimulated damage. All tested compounds decreased Aβ25–35-induced ROS generation and cell cycle arrest. In particular, baicalein exhibited the strongest antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Thus, evidence from in vitro studies showed increased oxidative stress-mediated by NF-kB in response to neurons exposed to Aβ; this increased oxidative stress resulted in the accumulation of lipid peroxides and neurodegeneration [ 92 ]. Moreover, many studies confirm that Aβ peptides stimulate NF-kB gene expression and its nuclear translocation [ 93 , 94 , 95 ].…”
Section: Aβ Vs Oxidative Stressmentioning
confidence: 99%
“…Thus, evidence from in vitro studies showed increased oxidative stress-mediated by NF-kB in response to neurons exposed to Aβ; this increased oxidative stress resulted in the accumulation of lipid peroxides and neurodegeneration [ 92 ]. Moreover, many studies confirm that Aβ peptides stimulate NF-kB gene expression and its nuclear translocation [ 93 , 94 , 95 ].…”
Section: Aβ Vs Oxidative Stressmentioning
confidence: 99%
“…Previous studies suggested that PDE2A and PDE4 expression was increased in brains of patients with AD and mouse models of AD, indicating that their involvement in AD pathology ( Nabavi et al, 2019 ; Tibbo et al, 2019 ). Recent studies suggest that baicalein prevents Aβ-induced memory deficits by attenuating inflammatory response and neuronal apoptosis ( Acquarone et al, 2019 ; Ji et al, 2020 ). However, whether the effects of baicalein on AD-related memory deficits are involved in regulation of PDE subtypes and the downstream signaling pathway remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent study showed that SB has potential therapeutic effects on coronavirus disease 2019 [ 26 ]. Moreover, baicalin and baicalein, which are the major bioactive compounds in SB, have demonstrated an important role in inhibiting the production of inflammatory cytokines [ 25 , 27 ], NF- κ B signalling [ 28 , 29 ], and c-fos expression [ 30 ] in multiple experimental models. These mechanisms are crucial in the pathophysiological processes of migraine.…”
Section: Discussionmentioning
confidence: 99%